Morphological changes of the intestinal mucosa of broilers and layers as affected by fasting before sample collection - Zavarize, K C [UNESP]; Sartori, José Roberto [UNESP]; Gonzales, E [UNESP]; Pezzato, Antonio Celso [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2012)
The present study aimed at evaluating the histo-morphological changes resulting from different fasting periods before the collection of tissue samples in different segments of the small intestine (duodenum, jejunum and ileum) of 7-d-old male chicks of a broiler and a layer strain. A completely randomized experimental design in in a 2x7 factorial arrangement, being two strains with different growth rates (Ross 308 and HyLine® W36) and seven fasting periods (0, 2, 4, 6, 8, 10 and 12 hours ), with six replicates, totaling 84 birds. The comparison of the morphometrics of the duodenum, jejunum and ileum of broiler and layer chicks demonstrated faster digestive tract development in broilers relative to layers. The fasting period caused morphological changes in the liver and small and large intestines in both strains. Therefore, it must be highlighted that in studies involving organ weights and intestinal morphometrics, birds must not be submitted to fasting before tissue collection.
Keywords: Fasting; intestine; morphology; organs; strain